1998
DOI: 10.1023/a:1018711420797
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Univariate and multivariate analyses were used to investigate intrinsic and contextual sources of coping variability among 90 patients with chronic pain. Pain coping strategies were assessed by the subscales of the Coping Strategies Questionnaire. Intrinsic variables included demographic characteristics and dispositional optimism. Contextual variables included pain-related variables and pain control appraisals. In univariate analyses, ethnicity was a statistically significant intrinsic source of variability fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For instance, pain catastrophizing, depressed mood, and neuroticism all exert deleterious effects on the experience of pain [1921], and a common pain psychology treatment goal involves reducing the negative impact of these factors. Despite the limited number of studies from which to draw conclusions [22, 23], Garofalo’s review led him to tentatively assert that preliminary evidence supports the positive effects of optimism on the experience of pain and its course of treatment. Over the past decade, the consensus that optimism positively influences the course and experience of acute and chronic pain as well as individuals’ responses to pain treatments has continued to grow.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, pain catastrophizing, depressed mood, and neuroticism all exert deleterious effects on the experience of pain [1921], and a common pain psychology treatment goal involves reducing the negative impact of these factors. Despite the limited number of studies from which to draw conclusions [22, 23], Garofalo’s review led him to tentatively assert that preliminary evidence supports the positive effects of optimism on the experience of pain and its course of treatment. Over the past decade, the consensus that optimism positively influences the course and experience of acute and chronic pain as well as individuals’ responses to pain treatments has continued to grow.…”
Section: Introductionmentioning
confidence: 99%
“…First, we examined the role of dispositional optimism in family stress processes for Mexican-origin mothers. Earlier research shows that coping styles and strategies can differ among ethnic groups (Njoku, Jason, & Torres-Harding, 2005;Novy, Nelson, Hetzel, Squitieri, & Kennington, 1998), and ethnic differ-ences have been found in how families function when facing stressful life events (Behnke et al, 2008). Cultural influences on optimism have also been found (e.g., Chang, 2001).…”
mentioning
confidence: 99%
“…The investigators hypothesized that-in contrast to pessimism, for which wishful thinking has a mediating effect-coping strategies might not be the mechanism by which optimism exerts its health-promoting effects. Novy et al (1998) observed two patterns of coping strategies among 90 chronic pain patients, most of whom had reported low back pain. The investigators found that a higher level of optimism was related to active-coping strategies.…”
Section: Optimism and Painmentioning
confidence: 94%
“…As evidence grows to suggest that optimism is an important mediator of stress and health, many now hypothesize that optimism could have significant effects on pain. Indeed, some research indicates that an optimistic disposition could lead to successful treatment of patients with pain (Gruen, 1972; Haerkaepaeae et al, 1996 Novy, Nelson, Hetzel, Squitieri, & Kennington, 1998). For an estimated 50 million Americans pain conditions are a major source of life stress (Turk, 1996).…”
Section: Optimism and Painmentioning
confidence: 99%